Diálogos entre urbanismo tático e moderação de tráfego no programa (Re)pensando Santana: desafios e potencialidades - Novis, Raquel Lourenço Mendes (2024)
Contemporary urban planning paradigms promote inclusive projects, prioritizing those who walk, in the transformations of existing road space, redesigning streets to provide greater comfort and safety for all users, focusing on people, considering and encouraging modal integration. This study analyzes the potential of the tactical urbanism intervention of the (Re)Pensando Santana program, located in Area 40 of the same neighborhood, and its impacts on walkability, implementation of traffic calming elements, accessibility and pedestrian safety. As a theoretical approach, three perspectives are considered, the first focuses on tactical urbanism, a model of intervention in urban space that promotes short-term transformations, authorized or not, that are quickly executed, cheap and easy to practice, and can be produced by society or by governments and companies, seeking quick answers. The second, on traffic calming, modifying the behavior of different modes of transport, increasing road safety and comfort for everyone, especially pedestrians. And finally, walkability, accessibility and pedestrian safety, qualities of the urban environment that allow and encourage walking as a means of transport. The method used is triangulation, with literature review, collection and analysis of data extracted from public administration, field visits, and individual interviews applied to managers participating in the program. As a result of this program, there were changes to calm traffic at two intersections in the Santana neighborhood and, although there is still a lack of a more emphatic way of gaining space for pedestrians, the importance of these experiences for increasing road safety must be highlighted